2017
DOI: 10.15255/cabeq.2014.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aeration and Type of Coagulant on Effectiveness in Removing Pollutants from Groundwater in the Process of Coagulation

Abstract: The subject of research was groundwater from Quaternary formations with high concentration of total iron, increased colour and turbidity, and an increased amount of organic substances and manganese. Successful purification of such water creates technological problems and is practically impossible to achieve by applying traditional groundwater treatment processes. One of the ways recommended for intensifying the removal of iron that occurs in the form of stable iron-organic compounds is the application of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…The inorganic monomeric aluminium represents their main fraction of aluminium after water treatment (62% of total). The analysis of literature information [13][14][15][16][17][18][19][20] [20][21][22][23] determine the quantitative share of individual hydrolysis products outside the hydrolysis conditions, to a large extent depending on the type of coagulant. Hydrolysis of aluminium cations, which are products of dissociation of non-prehydrolysed coagulants such as aluminium sulphate (VI) or sodium aluminate, takes place immediately after their contact with water.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic monomeric aluminium represents their main fraction of aluminium after water treatment (62% of total). The analysis of literature information [13][14][15][16][17][18][19][20] [20][21][22][23] determine the quantitative share of individual hydrolysis products outside the hydrolysis conditions, to a large extent depending on the type of coagulant. Hydrolysis of aluminium cations, which are products of dissociation of non-prehydrolysed coagulants such as aluminium sulphate (VI) or sodium aluminate, takes place immediately after their contact with water.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the research results obtained showed that the pH of water after coagulation with the PAXXL1911 coagulant (Z = 85%, Fe = 0.7%) ranged from 7.86 to 8.00 and with the PAXHP908 (Z = 85%, Fe < 0.01%) ranged from 7.85 to 8.00 for doses from 1 to 5 mgAl/dm 3 . The turbidity, colour and concentration of iron was also determined in the water after the coagulation process.…”
Section: Resultsmentioning
confidence: 99%
“…Dose of coagulants (Dc) was expressed in mgAl/dm 3 or mgFe/dm 3 and dosed in the amount of 1.78 mgAl(Fe)/dm 3 . Dose of coagulants was determined on the basis of previously conducted research [6][7][8][9][10][11][12][13]. Apart from primary coagulants, also the solution of semi-anionic polyelectrolyte (Praestol 2540) of 1000 mg/dm 3 concentration was dosed in the amount of Dp = 0.15 or 0.25 mg/dm 3 , in advance or with delay in relation to the time of coagulant dosing.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of water aeration, agglomerates of ferrous hydroxide (III) with good sedimentation properties are not produced because the natural organic matter present in the water creates water-soluble coloured bonds of a colloidal character with ions and ferric compounds [2,21]. Due to the fact that in the studies previously conducted by the author [6][7][8][9][10][11][12][13] ferric compounds (III) created as a result of aeration agglomerated with difficulty due to the presence of organic substances, this study attempted to intensify flocculation by using polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%